Suicide risk and mortality among patients with cancers of the digestive system: a systematic review and meta-analysis - Wang, Yebin; Yang, Xiaotian; Song, Mengyao; Li, Yipu; Jiao, Dechao; Zhou, Xueliang (Frontiers in Oncology, 2026)
BackgroundAlthough significant strides have been made in cancer therapy, studies show that suicide rates among digestive cancer patients compared to the general population remain controversial, and specific risk factors are not clearly defined. Therefore, we conducted a systematic review and meta-analysis of the standardized mortality ratios (SMRs) in patients with digestive system cancer.MethodsPubMed, Embase, Web of Science and Cochran Library databases were searched for relevant articles up to June 2025. We assessed SMRs by cancer type, sex, cancer prognosis, time since diagnosis, geographic region and year of recruitment. We performed meta-analysis by random effects model and evaluated heterogeneity using I² statistic. Publication bias was performed by funnel plots, Edger’s and B egg’s tests.Results12 cohort studies comprising 6763452 digestive cancer patients were eligible. The total SMR in this population was (SMR = 2.25, 95% CI = 1.89-2.66, P < 0.000). The SMRs were significantly increased for esophageal (SMR = 3.35, 95% CI = 2.37-4.75, P < 0.000), pancreatic (SMR = 3.87, 95% CI = 2.33-6.41, P < 0.000), stomach (SMR = 2.10, 95% CI = 1.81-2.43, P < 0.000), liver (SMR = 1.89, 95% CI = 1.38-2.59, P = 0.066) and colorectum (SMR = 1.57, 95% CI = 1.36-1.81, P < 0.000) cancers. Furthermore, the SMRs exhibit significant variations influenced by other contributing factors.ConclusionsDue to various suicide risk factors, the SMRs among digestive cancer patients surpasses that of the general population by more than double. Hence, heightened psychological support is warranted for these patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420261288056, identifier CRD420261288056.